Implementation of Slowly Changing Dimension to Data Warehouse to Manage Marketing Campaigns in Banks - WANG, Lihui (Institutional Knowledge at Singapore Management University, 2013)
Management of updating and recording campaign leads in data warehouse of any banking environment is complex especially with multiple campaigns are active simultaneously. As a way to avoid overly contacting customers for sales-based marketing contacts, the concept of Recency Frame is introduced to “lock” the customers who are targeted in Sales-based campaign for a specified time period. During this Recency Frame, the customer cannot be targeted by other Sales-based campaign under the same channel. This approach increased the difficulties of managing the customers’ data with proper data updating and storing and procedures have to be placed and made sufficiently robust for incorporation of the recency rules. In this paper, we will illustrate the concept of slowly changing dimension and how it could be utilized in an innovative manner in the data warehouse of a bank to update and maintain campaign records of customers.